The role of the media in spreading hooliganism - Al-Zahrani, Walid bin Attia; Al-Shetry, Abdul Aziz bin Hamoud (Arab Journal for Sciences and Research Publishing, 2016)
This study aimed to investigate the extent to which high school students in the city of Riyadh are exposed to sports channels and the role of the media in spreading hooliganism (sports fanaticism), where the media can be considered as the public school that continues the work of sports institutions.
Keywords: Role; media; Hooliganism; excitement